Connecting Judgment Process and Accuracy of Student Teachers: Differences in Observation and Student Engagement Cues to Assess Student Characteristics - Schnitzler, Katharina; Holzberger, Doris; Seidel, Tina (Frontiers in Education, 2020)
Teachers' ability to assess student cognitive and motivational-affective characteristics is a requirement to support individual students with adaptive teaching. However, teachers have difficulty in assessing the diversity among their students in terms of the intra-individual combinations of these characteristics in student profiles. Reasons for this challenge are assumed to lie in the behavioral and cognitive activities behind judgment processes. Particularly, the observation and utilization of diagnostic student cues, such as student engagement, might be an important factor. Hence, we investigated how student teachers with high and low judgment accuracy differ with regard to their eye movements as a behavioral and utilization of student cues as a cognitive activity. Forty-three participating student teachers observed a video vignette showing parts of a mathematics lesson to assess student characteristics of five target students, and reported which cues they used to form their judgment. Meanwhile, eye movements were tracked. Student teachers showed substantial diversity in their judgment accuracy. Those with a high judgment accuracy showed slight tendencies toward a more “experienced” pattern of eye movements with a higher number of fixations and shorter average fixation duration. Although all participants favored diagnostic student cues for their assessments, an epistemic network analysis indicated that student teachers with a high judgment accuracy utilized combinations of diagnostic student cues that clearly pointed to specific student profiles. Those with a low judgment accuracy had difficulty using distinct combinations of diagnostic cues. Findings highlight the power of behavioral and cognitive activities in judgment processes for explaining teacher performance of judgment accuracy.